An Unusual Cause of an Incidental Lung Mass - Lindsay M Lawson; Pari Tiwari; J Douglas Filipenko (Canadian Respiratory Journal)
A 52-year-old woman was found to have a mass measuring 1 cm in diameter with radiographic features of a carcinoid tumour in the left lung during work-up for chest pain. Wedge excision of the lesion revealed a leiomyoma that had a similar histological appearance to uterine 'fibroids' removed eight years previously. This case is an example of benign metastasizing leiomyoma, an unusual lesion of uncertain etiopathogenesis.